การพัฒนาการบริหารจัดการสหกรณ์การเกษตรของกรมส่งเสริมสหกรณ์ตามปรัชญาของเศรษฐกิจพอเพียง (THE DEVELOPMENT OF AGRICULTURAL COOPERATIVE ADMINISTRATION FOR THE COOPERATIVE PROMOTION DEPARTMENT ACCORDING TO THE SUFFICIENCY ECONOMY PHILOSOPHY) - ศรีศิลปวงศ์ เกรียงศักดิ์ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2016)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษา (1) ปัญหาเกี่ยวกับการบริหารจัดการสหกรณ์การเกษตรของกรมส่งเสริมสหกรณ์ตามปรัชญาของเศรษฐกิจพอเพียง (2) แนวทางการพัฒนาการบริหารจัดการสหกรณ์การเกษตรของกรมส่งเสริมสหกรณ์ตามปรัชญาของเศรษฐกิจพอเพียง และ (3) ตัวแบบการพัฒนาการบริหารจัดการสหกรณ์การเกษตรของกรมส่งเสริมสหกรณ์ตามปรัชญาของเศรษฐกิจพอเพียง การศึกษาครั้งนี้เป็นการวิจัยแบบผสมโดยใช้วิธีการวิจัยเชิงปริมาณเป็นหลัก เน้นการวิจัยเชิงสำรวจ โดยใช้แบบสอบถามซึ่งผ่านการทดสอบเพื่อหาความเที่ยงตรงของแบบสอบถามได้ค่า IOC ที่ระดับ 0.86 และค่าความเชื่อถือได้ของแบบสอบถามที่ระดับ 0.95 ประชากรที่ศึกษา ได้แก่ สมาชิกสหกรณ์การเกษตรในพื้นที่อำเภอดอนตูม จังหวัดนครปฐม ทั้งหมด จำนวน 2,193 คน การเก็บรวบรวมข้อมูลสนามดำเนินการระหว่างวันที่ 15 พฤษภาคม 2557 ถึง วันที่ 30 พฤษภาคม 2557 เก็บรวบรวมแบบสอบถามที่สมบูรณ์กลับคืนมาได้จำนวน 1,938 ชุด คิดเป็นร้อยละ 88.37 ของประชากรทั้งหมดที่ศึกษา สำหรับสถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน ค่าการถดถอยพหุคูณ และการหาค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน นอกจากนี้ยังมีการสัมภาษณ์แนวลึกเฉพาะผู้เชี่ยวชาญเพื่อให้ได้ข้อมูลเชิงคุณภาพอีกด้วย ผลการศึกษาพบว่า (1) ปัญหาที่สำคัญ ด้านความมีเหตุผล คือ สหกรณ์การเกษตรไม่ได้ส่งเสริมและดูแลสมาชิกสหกรณ์การเกษตรให้เข้ามามีส่วนร่วมในการวางแผนพัฒนาการเกษตรที่สอดคล้องกับความต้องการของสมาชิกสหกรณ์การเกษตร (2) แนวทางการพัฒนาการบริหารจัดการที่สำคัญ คือ สหกรณ์การเกษตรควรส่งเสริมและดูแลสมาชิกสหกรณ์การเกษตรในพื้นที่ให้เข้ามามีส่วนร่วมในการวางแผนพัฒนาการเกษตรที่สอดคล้องกับความต้องการของสมาชิกสหกรณ์การเกษตร และ (3) ตัวแบบการพัฒนาการบริหารจัดการตามปรัชญาของเศรษฐกิจพอเพียง ควรเน้นด้านความมีเหตุผล และด้านอื่น ได้แก่ ด้านความพอประมาณ ด้านการเสริมสร้างความรู้คู่คุณธรรม และด้านการมีภูมิคุ้มกัน คำสำคัญ: การพัฒนา การบริหารจัดการ สหกรณ์การเกษตร กรมส่งเสริมสหกรณ์ ปรัชญาของเศรษฐกิจพอเพียง The main objectives of this research were to study (1) problems of the administration of agricultural cooperative for the Cooperative Promotion Department according to the Sufficiency Economy Philosophy, (2) to proposr development guidelines for the administration of agricultural cooperative for the Cooperative Promotion Department according to the Sufficiency Economy Philosophy, and (3) to develop administrative model for the administration of agricultural cooperative for the Cooperative Promotion Department according to the Sufficiency Economy Philosophy. The study employed a mixed research method with emphasis on survey research using questionnaires that had passed pre-testing with validity check at 0.86 level and reliability check at 0.95 level. Population surveyed included the entire population of 2,193 agricultural cooperative members in the Don Dum District, Nakorn Prathom Province. Field data collection was conducted from May 15th to May 30th, 2014. 1,938 sets of completed questionnaires were collected, representing 88.37% of the population surveyed. Statistics used were mean, standard deviation, multiple regression, and Pearson’s correlation. An in-depth interview of experts for qualitative information was also conducted. The study findings showed that (1) a major problem was the reasonableness aspect because the Cooperative Promotion Department did not encourage cooperative members to take active roles in the planning process of agricultural projects fulfilling the requirements of cooperative members, (2) a major administration development guideline for the Agricultural Promotion Department was to encourage cooperative members to take active roles in the planning process of agricultural projects fulfilling the requirements of cooperative members, and (3) the administrative model of development for administration of agricultural cooperative for the Cooperative Promotion Department according to the Sufficiency Economy Philosophy should give strong emphasis to the reasonableness aspect as well as other aspects such as moderation, self-immunity, knowledge and moral. Keywords: Development, administration, agricultural cooperative, Cooperative Promotion Department, Sufficiency Economy Philosophy